(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Swami Vivekananda might be called as the father of modern Indian Nationalism. He was a true nationalist. Swami Vivekananda’s contemporary social and religious reformer taught the people about metaphysics but Vivekananda’s theory was different. He says, “An empty stomach is no good for religion.” He considered first duty of us is duty for our motherland. He took motherland as deity to be worshipped. He took every Indian as his brother. He believed that the main cause of India’s downfall is the exploitation of poor masses. By upliftment of poor and downtrodden, we can establish nationalism. He called the people as well as Indian youth’ Arise, awake and stop not till the goal is reached. He believed that it was very important to arise a feeling of nationalism among Indian people. By lectures and writings Vivekananda imparted a sense of pride, cultural confidence to Indian people. The Rama Krishna mission also became a central point of Indians’ conspiracy. He also made an influence on Indian revolutioners like Gandhiji, Subhash Chandra Bose, R. N. Tagore.